MORAL SENSITIVITY OF NURSES ASSESSED THROUGH SCOPING REVIE - Carlise Rigon Dalla Nora; Elma Zoboli; Margarida Maria Vieira (Universidade Federal do Paraná, 2017)
This study aims to identify the factors that influence the moral sensitivity of nurses in health services, based on publications on the theme. Therefore, we conducted a scoping review for the August-December 2015 period in health literature databases. Theoretical and original studies with nursing students and health teams with nurses, published in English, Spanish and Portuguese, were included. The sample consisted of 28 studies. Two categories emerged from the analysis: "personal factors" and "contextual factors" of moral sensitivity. We concluded that "personal factors" have the greatest impact on the formation/expression of moral sensitivity of nurses. Moral sensibility has a multidimensional nature and must be complemented with nurse's training to identify and deal responsibly and prudently with the ethical problems of clinical practice.